أثر التعلم عن بعد في تحقيق نواتج التعلم أثناء جائحة كورونا: منصة مدرستي أنموذجا - آل كاسي، عبدالله بن علي بن معيض; خواجي، أيمن طاهر محمد; العمري، أحمد خضران; خصاونة، محمد أحمد سليم; الخصاونة، فادي ماهر صالح (جامعة تبوك, 2023)
هدف هذا البحث إلى التعرف على أثر التعليم عن بعد من خلال منصة (مدرستي) في تحقيق نواتج التعلم المعرفية أثناء جائحة كورونا لدى طلبة المرحلتين الابتدائية والمتوسطة بالمدارس الحكومية بإدارة تعليم (صبيا)، والكشف عن وجود فروق ذات دلالة إحصائية في نواتج التعلم المعرفية أثناء جائحة كورونا لدى طلبة المرحلتين الابتدائية والمتوسطة بالمدارس الحكومية بإدارة تعليم (صبيا) - تعزى لمتغيري النوع (بنين - بنات)، والموقع الجغرافي لمكاتب التعليم (نائية - غير نائية). ولتحقيق هذه الأهداف؛ اعتمد البحث على المنهج الوصفي المسحي، الذي تم من خلاله جمع البيانات بفحص وتحليل درجات طلبة الصفين الرابع الابتدائي والثاني المتوسط بالاختبارات التحصيلية بمواد العلوم والرياضيات واللغة العربية). وتمثلت عينة البحث في طلبة الصف الرابع الابتدائي بمكاتب التعليم التسعة بإدارة تعليم (صبيا)، والبالغ عددهم (9302) طالبا وطالبة، في حين بلغ عدد طلبة الصف الثاني المتوسط (6802) طالبا وطالبة. وأظهرت نتائج البحث وجود تأثير كبير للتعليم عن بعد عبر منصة (مدرستي) في تحقيق نواتج التعلم المعرفية لدى طلبة الصف الرابع الابتدائي، في حين لم يوجد تأثير للتعليم عن بعد عبر منصة (مدرستي) في تحقيق نواتج التعلم المعرفية لدى طلبة الصف الثاني المتوسط. كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية في تحقيق نواتج التعلم المعرفية أثناء جائحة كورونا لدى طلبة الصفين الرابع الابتدائي والثاني المتوسط بالمدارس الحكومية بإدارة تعليم (صبيا) - تعزى لمتغيري النوع والموقع الجغرافي لمكاتب التعليم. لذا يوصي الباحث بضرورة توجيه أنظار مسؤولي إدارة تعليم (صبيا) إلى ضرورة تحسين عناصر ومكونات منصة (مدرستي) للمرحلة المتوسطة، بما يساعد على زيادة أثرها في التحصيل الدراسي لدى الطلبة في هذه المرحلة. This study aimed at identifying the impact of distance education through the (Madrasati) platform in achieving cognitive learning outcomes during the Corona pandemic among primary and middle school students in public schools in Sabya. The study also aimed at revealing the presence of statistically significant differences in cognitive learning outcomes during the Corona pandemic among primary and middle school students due to gender variables and the geographical location of education offices (remote - non-remote). To achieve these goals, the research relied on the descriptive survey method, through which data were collected by examining and analyzing the grades of students in the fourth primary and second intermediate grades in achievement tests in science, mathematics, and Arabic language. The sample of the research was represented by the students of the fourth grade of primary school in the nine education offices in the Department of Education (Sabya), and their number was (9302) male and female students, while the number of students in the second intermediate grade was (6802) male and female students. The results showed that there was a significant effect of distance education via the (Madrasati) platform in achieving cognitive learning outcomes for fourthgrade students, while there was no effect of distance education via the (Madrasati) platform in achieving cognitive learning outcomes for second-grade students in the middle school. The results also showed that there were no statistically significant differences in the achievement of cognitive learning outcomes during the Corona pandemic among students of the fourth primary and second intermediate grades due to the variables of gender and geographical location of education offices. Therefore, the researcher recommends the need to direct the attention of the Sabya Education Department officials to the need to improve the elements and components of the (Madrasati) platform for the intermediate stage, in order to help increase its impact on the academic achievement of students at this stage.
Keywords: التعلم عن بعد -- المنصات التعليمية -- نواتج التعلم -- جائحة كورونا "كوفيد-19" -- المدارس السعودية